Mobilizing the White: White Nationalism and Congressional Politics in the American South. Issue 5 (September 2022) - Weiner, Amanda; Zellman, Ariel
To what extent do white nationalists influence Congressional representative conservatism? Although ethnocentrism, out-group prejudice, and racial threats strongly predict American political attitudes and voter behavior, how social movements predicated on these beliefs shape political outcomes is rarely considered. We argue that white nationalist activities significantly contribute to the radicalization of Congressional representatives' policy agendas in a manner non-reducible to demographic or socioeconomic conditions. By mobilizing white voters against racial status threats, they indirectly compel politicians to adopt more radically conservative agendas. We quantitatively test these propositions by examining distributions of white nationalist groups in the American South against Congressional representative conservatism from 2010–2017. Analyses reveal that white nationalists indeed appear to significantly impact representative radical conservatism, even controlling for numerous factors commonly theorized to explain their rise. In doing so, we contribute to emerging insights on the political influence of the radical right on the contemporary American conservative "mainstream."